Islamic finance and NCCs: Comparative insights from Malaysia, Indonesia, and El Salvador - Zull Kepili, Ema Izati; Nik Azman, Nik Hadiyan (‘Abqari Journal, 2025)
The growing interest in national cryptocurrencies (NCCs), also known as central bank digital currencies (CBDCs), has prompted policymakers worldwide to explore their potential in enhancing monetary efficiency, financial inclusion, and digital sovereignty. Yet, most frameworks for evaluating NCC readiness remain heavily skewed toward technical and regulatory perspectives, overlooking crucial dimensions such as socio-cultural alignment and ethical compliance—particularly in Islamic finance jurisdictions. This conceptual paper proposes a four-pillar framework to assess NCC readiness in Muslim-majority countries, drawing on case studies from Malaysia and Indonesia, and contrasting them with El Salvador’s experience. The proposed pillars—technological infrastructure, regulatory adaptability, monetary policy integration, and socio-cultural and Shariah alignment—are examined through an interdisciplinary lens combining technology adoption, institutional theory, and Islamic finance principles. Findings highlight the need for a culturally grounded, ethically compliant approach to NCC implementation, especially in ASEAN economies navigating both digital transformation and geopolitical uncertainty. This study offers strategic insights for central banks, regulators, and Shariah bodies seeking inclusive and sustainable pathways in the evolving digital currency landscape. Also, this study integrates Maqasid al-Shariah into NCC readiness assessment and offers comparative insights contrasting El Salvador with Malaysia and Indonesia.